Dear Customer, Thank You for Your Review: The Service Failure-recovery Dyadic Interactions in the Restaurant Industry - Premordia, Inda; Gál, Timea (International Review of Management and Marketing, 2021)
The advent of Web 2.0 has encouraged restaurant customers to post online reviews, and oftentimes, not in favor of the company. When a service failure occurs, the customer may voice their complaints publicly online. The company, on the other hand, has the opportunity to respond to these complaints and use it as a part of their service recovery strategy. While some companies are responding to negative reviews, only a few have the knowledge on how to do it effectively. Built on perceived justice framework: distributive, procedural, interactional; and service failure severity type: outcome-process, major-minor, present study intends to understand different resolution styles adopted by the company to varying types of customer complaint. The findings outline: (1) the vast majority of the company exhibits only a low level of responsiveness to complaints; (2) the most severe complaints deal with psychological loss, physical loss and major incidents lead to frustration; (3) however, different strategies depending upon service failure severity are yet to be implemented by the company; (4) while components in interactional justice are mostly performed, rude responses are also frequently applied. Further elaboration of the findings and insights for marketing practice are discussed in the text. Keywords: Service recovery; Service failure severity; Online customer reviews; Restaurant industry JEL Classifications: L83, L84, Z33 DOI: https://doi.org/10.32479/irmm.11257